Long-term use of investigational β-Hydroxybutyrate salts in children with multiple acyl-CoA dehydrogenase or pyruvate dehydrogenase deficiency - Morris, Andrew A.M.; Cuenoud, Bernard; Delerive, Philippe; Mundy, Helen; Schwahn, Bernd C. (Molecular genetics and metabolism reports, 2024)
Several disorders of energy metabolism have been treated with exogenous ketone bodies. The benefit of this treatment is best documented in multiple acyl-CoA dehydrogenase deficiency (MADD) (MIM#231680). One might also expect ketone bodies to help in other disorders with impaired ketogenesis or in conditions that profit from a ketogenic diet. Here, we report the use of a novel preparation of dextro-β-hydroxybutyrate (D-βHB) salts in two cases of MADD and one case of pyruvate dehydrogenase (PDH) deficiency (MIM#312170). The two patients with MADD had previously been on a racemic mixture of D- and L‑sodium hydroxybutyrate. Patient #1 found D-βHB more palatable, and the change in formulation corrected hypernatraemia in patient #2. The patient with PDH deficiency was on a ketogenic diet but had not previously been given hydroxybutyrate. In this case, the addition of D-βHB improved ketosis. We conclude that NHS101 is a good candidate for further clinical studies in this group of diseases of inborn errors of metabolism.